Sobre a solidão e o tornar-se si mesmo: aproximações e distinções entre Friedrich Nietzsche e Carl Rogers - Ponte, Carlos Roger Sales da (2020)
Taking as philosophical markers and dialogical pairs, the thought of the German philosopher, Friedrich Nietzsche (1844 1900) and the North American psychologist, Carl R. Rogers (1902 1987), this research aims to show loneliness in quite different outlines. that one sees in the prejudices about her in ordinary lif e. In both authors it is possible to perceive a positivity in loneliness, understood as the need for healthy human recollection to listen to their experiences, seeking a singularity that seems to be lacking. In Nietzsche, a lone thinker, it does not seem p ossible to make contact with other humans without endangering all the richness of authenticity that the human might have achieved without sacrificing loneliness. This requires those who want to start a movement to become what they are, to mark a certain di stance from social life in order to respond to that call to become. In Rogers, a thinker of human relations, there is the possibility of becoming oneself (which he calls becoming a person) through dialogical mediation, in exchanging experiences that would have as one of his goals, to come into deeper contact with one another. Those experiences and then find a safe support to try other ways of living, also authentic. More clearly: as long as there is no loneliness to feel and hear where life itself is trappe d, obstructed in its vital conformations, the human will not stand in the movement of opening a horizon in search of one becoming oneself; of freedom from the multiplicity of one's experiences; far exceeding the cultural injunctions that insist on conformi ng to what is set. It is in this confluence between the experiences of loneliness and becoming oneself that the dialogue between Nietzsche and Rogers finds its origin and viability.